2014
DOI: 10.1016/j.addbeh.2013.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Caffeinated alcohol consumption profiles and associations with use severity and outcome expectancies

Abstract: Growing evidence suggests that the consumption of caffeinated alcoholic beverages (CAB) may be riskier than alcohol alone. Efforts to identify patterns of CAB use and the correlates of such drinking patterns could further our conceptualization of and intervention for this health issue. Consequently, the current study aimed to (1) identify distinct classes of CAB users, (2) examine differences between classes on measures of alcohol and caffeine problems, and (3) compare distinct classes of CAB users on caffeine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 46 publications
0
29
0
Order By: Relevance
“…Regarding the limitations of this work, we note that, although mixed structural equation models help to explain or detect influences in variables such as academic performance (Berlin, Williams, & Parra, 2014;Lau-Barraco, Milletich, & Linden, 2014), the categorization or establishment of groups or clusters of continuous variables can lead to a loss of information, although it allows understanding more clearly the influence of a variable, as observed in this study. In this sense, this technique of data analysis shows that, in subjects who critically analyze less class contents and who have worse academic performance, the relationship between these variables is greater.…”
Section: Discussionmentioning
confidence: 86%
“…Regarding the limitations of this work, we note that, although mixed structural equation models help to explain or detect influences in variables such as academic performance (Berlin, Williams, & Parra, 2014;Lau-Barraco, Milletich, & Linden, 2014), the categorization or establishment of groups or clusters of continuous variables can lead to a loss of information, although it allows understanding more clearly the influence of a variable, as observed in this study. In this sense, this technique of data analysis shows that, in subjects who critically analyze less class contents and who have worse academic performance, the relationship between these variables is greater.…”
Section: Discussionmentioning
confidence: 86%
“…Regarding alcohol consumption, participants reported the number of non-caffeinated alcoholic drinks typically consumed each day during a typical week over the previous three months. A separate, modified DDQ asked about typical CAB use (e.g., Red Bull and vodka, rum and Coke) during a typical week (e.g., Lau-Barraco & Linden, 2014; Lau-Barraco, Milletich, & Linden, 2014). The DDQ has adequate convergent validity with self-report measures of alcohol-related problems (Collins, Bradizza, & Vincent, 2007; Collins, Koutsky, & Izzo, 2000; Collins & Lapp, 1992).…”
Section: Methodsmentioning
confidence: 99%
“…While no other information (including significance tests) was provided in their study, it provides an impetus for suggesting that there may be a connection between AmED consumption and patterns of alcohol dependence. A more recent study by Lau-Barraco, Milletich, and Linden (2013) examined caffeinated alcoholic beverages (CABs) and alcohol severity (defined by Alcohol Use Disorders Identification Test [AUDIT] scores greater than 8). Lau- Barraco et al (2013) divided participants into low/high groups in terms of alcohol use and CAB use.…”
Section: Amed and Patterns Of Alcohol Dependencementioning
confidence: 99%
“…A more recent study by Lau-Barraco, Milletich, and Linden (2013) examined caffeinated alcoholic beverages (CABs) and alcohol severity (defined by Alcohol Use Disorders Identification Test [AUDIT] scores greater than 8). Lau- Barraco et al (2013) divided participants into low/high groups in terms of alcohol use and CAB use. Their analysis found that high CAB/high alcohol consumers had significantly higher AUDIT scores than their low alcohol/low CAB group.…”
Section: Amed and Patterns Of Alcohol Dependencementioning
confidence: 99%